Stifle Joint Rotational Variation in Extended Stifles in Healthy Dogs Undergoing Computed Tomography Examinations - Allberg, Clara M.; McEvoy, Fintan J.; Buelund, Lene E.; Miles, James E. (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objectives The aim of this study was to evaluate stifle joint rotational stability in response to body position and repositioning in dogs undergoing computed tomography (CT).Materials and Methods Nine dogs (18 stifles) with no history or clinical signs of stifle injury undergoing CT examinations for other reasons were included in the study. Dogs were positioned in alternating dorsal and sternal recumbency with the pelvic limbs extended caudally and unrestrained, for a total of four examinations. Scans included the entire tibia and distal femur. Using defined landmarks on the tibia and femur, stifle joint rotational angles were measured from multiplanar reconstructions made by two independent observers, and repositioning effects and intra- and interobserver agreement evaluated.Results Repositioning produced repeatable stifle joint rotational angles (pooled within-subject standard deviations of 0.9° and 1.4°) and intraobserver repeatability was good (within-subject standard deviations 1.4°), but interobserver agreement was poor. Dorsal and sternal positioning produced equivalent results.Clinical Significance The results indicate that little rotation occurs in the healthy extended canine stifle joint during positioning for CT and support CT as a method for assessing limb alignment around the stifle joint, provided that the limb distal to the femorotibial joint is unrestrained. Clinically, it is likely that measured changes in rotational angles across (and distant to) the stifle joint are real, rather than being due to rotation artefact during imaging.
Keywords: computed tomography; dogs; stifle joint